Pengaruh Profitabilitas, Manajemen Laba, dan Ukuran Perusahaan terhadap Tax Avoidance pada Perusahaan Manufaktur - Sukanto, Albertus; Hartanti, Emmiliana (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to empirically examine how the effect of profitability, earnings management, and firm size on tax avoidance. the population in this study were all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2014-2017. Sample selection method using purposive sampling method in the selection of samples and obtained the number of research samples as many as 65 companies with a total of 260 observational data. The data analysis method used in this study is multiple regression analysis using SPSS version 24. The results show that partially earnings management affects tax avoidance. Profitability and company size do not affect tax avoidance. Simultaneously profitability, earnings management, and company size do not affect tax avoidance